A case of a patient with exacerbation of interstitial lung disease whose activities of daily living were improved by pulmonary rehabilitation with neuromuscular electrical stimulation - 鈴木 翔太; 宇賀 大祐; 笛木 直人; 土橋 邦生 (Journal of respiratory physical therapy, 2024)
Introduction: We report a case of a patient with severe hypoxemia after exacerbation of interstitial lung disease (ILD), whose activities of daily living improved with the use of neuromuscular electrical stimulation (NMES).Case presentation: The patient, a 70-year-old male, was hospitalized for exacerbation of ILD, and physical therapy was started on the 15th day of hospitalization. Transferring was possible with light assistance, but walking was difficult. He was independent in eating and used a urinal and a bedpan for defecation. Transcutaneous arterial blood oxygen saturation decreased from 95% to 89% during sitting and standing motions while inhaling 6 L/min of oxygen. Since high-intensity exercise therapy was difficult, NMES was started on the 36th day of hospitalization, taking hypoxemia into consideration.Results: Isometric knee extension muscle strength improved by 4.3-6.2 kgf and continuous walking distance improved to 40 m. The patient became independent in activities of daily living and was discharged home.Conclusion: For patients following an exacerbation of ILD, the combined use of NMES, considering exertional hypoxemia, may help improve physical function and activities of daily living.